Anterior Spinal Artery Syndrome in a 14-Year-Old Boy - Watermeyer, Fabian; Stampfli, Martha L.; Hahn, Markus; Markart, Stefan; Gessler, Peter (Journal of Child Science, 2023)
Acute flaccid paralysis caused by anterior spinal artery syndrome (ASAS) is rare in children. It typically manifests as bilateral loss of motor function, pain, and temperature sensation below the level of occlusion, with relatively little impairment in proprioception and vibration sense. We present such a case in a 14-year-old child who presented with a sudden onset of neck pain followed by the typical symptoms of ASAS with impaired breathing due to the height of the lesion, which was found in the magnetic resonance imaging examination at the level of C1–5. An initially suspected thrombogenic cause proved inapplicable. Ultimately, despite extensive diagnosis, as in most cases of ASAS in children, the cause remains unclear.
Keywords: acute flaccid paralysis; spinal cord infarction; anterior spinal artery syndrome; neck pain; thrombolysis